TWO DESCENTS OF FRENCH REVOLUTION : A COMCOMPARISON ANALYSIS OF LIBERALISM AND CONSERVATISM THROUGH BASIC NOTIONS (Third Sector Social Economic Review, 2019)
Ideologies come to life as a result of developments that occurred after the Enlightenment and the French Revolution. Modernity and Enlightenment caused to a major transformation from science to social life, and the progressive, devastating and transformative influence of the resulting French Revolution has brought to life ideologies. In a common ground, ideologies hold a claim to the use of power. Each presents a vision of world. Ideologies present different world views about the type of political power, the form of government, who will govern, how and for what boundaries / boundlessness. This study aims to reveal the similarities and differences of the two ideologies that existed after the French Revolution, that is, conservatism and liberalism in terms of freedom, individual, society, market, state and its management.
Keywords: Ideologie; enlightenment; liberalism; conservatism; freedom; individual; society; French Revolution